Uso de placas oclusoras de palato em pacientes com fissuras labiopalatinas - Nunes, Rodrigo Sant`Ana (2012)
The objective of this study was to evaluate the effectiveness in the use of plates occlusion of the palate in patients with unilateral cleft lip and palate classifying occlusion second index Atack. In an evaluation of approximately 300 records of patients born between the years 2003 to 2006 in the treatment HMNSL-RJ. Found 74 patients with unilateral CLP underwent the use of plates occlusion of the palate. Following a strict inclusion criteria in search of a homogeneous sample could be selected orthodontic plaster models of 06 patients aged between 05 and 07 years, of both sexes, who made regular use of the palate plate occlusion and underwent primary lip repair surgeries in one and palatoplasty. The result was a prevalence of 66,6% of the sample classified as index Atack 1 (excellent). Conclusion: due to this high rate of absence of crossbite index (Atack 1) enabled thereby to this study suggest that the use of pre surgical orthopedic through the plates occlusion of the palate is efficient without negative interference on the occlusal relationship of the patients.